(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
On the shelves of the Ambrosiana Library in Milan and on those of the Marciana Library in Venice lies an oration in praise of Caterina Visconti, composed and delivered by the Celestine monk Taddeo Airoldi, probably commissioned by his son Filippo Maria in 1426 (?). A text that can contribute to highlighting new, unpublished aspects regarding the importance of the Duchess of Milan during the period of her regency after the death of her husband and first Duke of Milan Gian Galeazzo. A useful source also for obtaining valuable information on Catherine’s ’human’ side. At the same time, this oration by Taddeo Airoldi, which also presents similarities with the works of Christine de Pizan, can represent an extremely significant document also as regards the evolution of the female eulogy and the biographies of famous women, in particular as intermediate stage between the emulations of the portraits of Giovanni Boccaccio’s De mulieribus claris and the more articulated late fifteenth and sixteenth century results of the laudatory-biographical genre centered on the most noble and illustrious women.